Simulation of Covid-19 Spread in Malaysia and Italy Using SIR Model - CHAKNGARI, NUR HIDAYAH; IBRAHIM, NORZURIA (Enhanced Knowledge in Sciences and Technology, 2023)
The spread of the novel coronavirus disease (Covid-19) has created a chaos across the world. The disease continues to spread in all countries. The use of mathematical models in public health plays an important role in many aspects, such as rapidly visualization epidemiological information, monitoring, predicting and estimating the spread of disease, and supporting decision-making to prevent and control the pandemics. The objectives of this study are to simulate Covid-19 spreading in Malaysia using Susceptible-Infected-Recovered (SIR) model between 2021 and 2022, to simulate the Covid-19 spreading in Malaysia and Italy using Susceptible-Infected-Recovered (SIR) model between 2021 and 2022 and to compare the data spreading of Covid-19 diseases in Malaysia and Italy between 2021 and 2022 using graph descriptions. The simulation of SIR model for Malaysia and Italy built with real data which obtained from Github Repository and Johns Hopkins University, respectively using MATLAB. Then, the simulation of the SIR models is compared to show the trend of the spreading Covid-19 in Malaysia and Italy between the two years. From two years comparison, the number of infections in 2021 is higher for Italy than Malaysia as the vaccination rate in Malaysia is increasing compared to Italy. Meanwhile, the number of infections in 2022 for Malaysia is higher than Italy due to the arrival of Omicron variants. In conclusion, spread of Covid-19 will increase in time and better understanding of this disease among people can be improved, so that the epidemiological curve can be flattened for both countries.